A systematic review of antimicrobial resistance of typhoidal Salmonella in India - Britto, Carl D. (Indian J Med Res, 2019)
BACKGROUND & OBJECTIVES: The temporal trends in the development of antimicrobial resistance (AMR) among Salmonella Typhi and Salmonella Paratyphi in India have not been systematically reported. We aimed to systematically review the temporal AMR trends (phenotypic and molecular mechanisms) in bacterial isolates from patients with enteric fever over two decades in India. METHODS: To identify trends in AMR in India, resistance patterns among 4611 individual S. Typhi isolates and 800 S. Paratyphi A isolates, reported from 1992 to 2017 in 40 publications, were analysed. Molecular resistance determinants were extracted from 22 publications and also reviewed in accordance with the PRISMA guidelines. Articles were sourced using a predefined search strategy from different databases. RESULTS: The analyses suggested that multidrug-resistant (MDR) enteric fever was declining in India and being replaced by fluoroquinolone (FQ) resistance. Mutations in gyrA and parC were key mechanisms responsible for FQ resistance, whereas MDR was largely driven by resistance determinants encoded on mobile genetic elements (plasmids, transposons). INTERPRETATION & CONCLUSIONS: The results reflect the effect of antimicrobial pressure which has been driving AMR in typhoidal Salmonella in India. Understanding these trends is important in planning future approaches to therapy, which serve as a baseline for assessment of the impact of new typhoid conjugate vaccines against these resistant organisms.